Editorial [Hot Topic: Antithrombotic Drug Design (Executive Editor: Hiroyuki Matsuno)] - Matsuno, Hiroyuki (Current Pharmaceutical Design, 2006)
Each of the major participants in the human hemostatic system, such as platelets, coagulation, fibrinolysis and vessel wall, interact with and influence each other. At the start of development of thrombus formation, platelets adhere and aggregate at the site of vascular injury. The formed platelet plug is gradually consolidated and stabilized by fibrin network (coagulation). Finally, the sequence in the life cycle of a thrombus is represented by healing of the damaged vessel wall and degradation of the thrombus by the fibrinolytic system. This cascade tries to outline how and to which extent these systems interact with the initial thrombus formation. Many scientists and physicians have investigated and are much interested in the processes and interactions involved. Because blood clotting in a vessel can result in ischemia and necrosis of perfused tissues, it is important that hemostatic system is carefully controlled. Moreover, fibrinolytic system is also concerned with proteolytic system. This phenomenon is recently worth notice on the activation of many physiological agonists, such as VEGF, FGF and TGF-β. In preparing this issue, we have focused on each section of hemostatic system and sought to provide a useful volume for researchers in this field. In the first article, Matsuno [1] widely describes a role of α2-antiplasmin (α2-AP) and also mentions about a new aspect of fibrinolytic inhibitors. α2-AP is a specific plasmin inhibitor and its physiological effects are well-known in the development and the degradation of thrombus formation. Recently, α2-AP has shown to significantly affect proteolytic formation in vivo and plays a role of vascular remodeling and heart failure via VEGF regulation. Moreover, the phenomena show the possibility that the other physiological substances are also affected by plasmin. Ueshima and Matsuo [2] focus on the fibrinolytic system in the second article. Fibrinolytic compounds have been used and now the new agents that activate the fibrinolytic system have been clinically applied for the thrombolytic therapy. Recently, some derivatives of t-PA have been developed to obtain the longer half-life than native t-PA and allowed to administer as the singlebolus. Further, the new fibrin-specific PA such as staphylokinase and bat-PA have been developed. Many attempts have been made to develop the drugs that would induce the release of t-PA from endothelial cells. The article of Oury and coworkers [3] analyzes in details, the ADP receptor on platelets. Adenine nucleotides, ADP and ATP, are co-released from dense granules during platelet activation, as well as from endothelial cells and damaged red blood cells following vascular injury. They focused on recent findings on the physiology of these platelet ADP and ATP receptors, their distinct downstream intracellular signaling pathways as well as on the available agonists, antagonists and inhibitors that allow their pharmacological discrimination. The paper of Ishisaki and Matsuno [4] stresses the current view that TGF-β family seems to play pivotal roles for the development of atherosclerosis. Especially, TGF-β and activin A play protective roles against the development of atherosclerotic plaques. On the other hand bone morphogenetic protein seems to play pivotal roles for the calcification of the atherosclerotic plaques. Moreover, it is debatable whether gene therapy modulating cellular signal transductions of TGF-β family is a useful tool for an inhibition of progression of atherosclerotic disease. Finally, Kanno and Matsuno [5] provide data on anti-thrombotic peptides isolated from heart shock proteins (HSPs). Some low molecular mass heat shock proteins (HSPs) appear to act as molecular chaperones. Especially, HSP20 shows significant effects on the prevention of thrombus formation via inhibition of thrombin. Moreover, 9 amino-acid sequences isolated from HSP20 or αB-crystallin significantly reduced platelet aggregation induced by TRAP, but not a PAR-4 agonist. These findings strongly suggest that HSP20 or αB-crystallin can act intercellularly to regulate platelet functions. In conclusion, the outstanding articles in this issue provide a current summary to the approach of regulation of hemostatic system that involves pathological thrombotic formation. We, therefore, believe that this issue opens a new aspect for researchers in this field. References [1] Matsuno H. α2-antiplasmin on cardiovascular diseases. Curr Pharm Design 2006; 12(7): 841-847. [2] Ueshima S, Matsuo O. Development of new fibrinolytic agents. Curr Pharm Design 2006; 12(7): 849-857. [3] Oury C, Toth-Zsamboki E, Vermylen J, Hoylaerts MF. The platelet ATP and ADP receptors. Curr Pharm Design 2006; 12(7): 859-875. [4] Ishisaki A, Matsuno H. Novel ideas of gene therapy for atheroscrelosis: Modulation of cellular signal transduction of TGF-β family. Curr Pharm Design 2006; 12(7): 877-886. [5] Kanno Y, Matsuno H. The possibility of novel antiplatelet peptides: the physiological ........